The Influence of Knowledge and Behavior of Student's Personal Listening Devices Usage On The Speech Frequency Hearing Threshold In Online Learning During The Pandemic Period - Rafidah, Rif'ah; Dasa Novita, Khuznita; Barasabha, Thareq (Jurnal Ilmu Kedokteran Keluarga, 2022)
During the Covid-19 pandemic, learning activities had to be done online, increasing audiovisual technology usage. Although there are many benefits of PLD usage, these devices also indirectly harm hearing. This study aims to determine the effect of students' knowledge, attitudes, and behaviour in PLD usage on the speech frequency hearing threshold. It was observational-analytic research through filling out questionnaires. The sample was the medical students who took online learning during the pandemic. The respondents were selected by consecutive sampling and according to the inclusion criteria. Bivariate analysis was performed using the chi-square test. The variables measured were knowledge, attitudes, the behaviour of PLD usage, and speech frequency hearing threshold. The results showed a relationship between knowledge in PLD usage and speech frequency hearing threshold (p-value < 0.05). In contrast, attitudes and behaviour did not find a relationship with the speech frequency hearing threshold (p-value > 0.05). This study concludes that there were incidences of Hearing loss in college students in the second year of the pandemic for various reasons, including PLD usage. There was an influence between knowledge regarding excessive PLD usage that can cause hearing loss. There was no effect on attitudes and behaviour of PLD usage on speech frequency hearing thresholds.   Abstrak Di masa pandemi Covid-19, kegiatan pembelajaran harus dilakukan secara daring sehingga penggunaan teknologi audiovisual meningkat. Meski banyak manfaat penggunaan PLD, perangkat ini juga secara tidak langsung membahayakan pendengaran. Penelitian ini bertujuan untuk mengetahui pengaruh pengetahuan, sikap, dan perilaku siswa dalam penggunaan PLD terhadap ambang dengar frekuensi bicara. Jenis penelitian ini adalah penelitian observasional-analitik melalui pengisian kuesioner. Sampelnya adalah mahasiswa kedokteran yang mengikuti pembelajaran daring selama pandemi. Responden dipilih dengan cara consecutive sampling dan sesuai dengan kriteria inklusi. Analisis bivariat dilakukan dengan menggunakan uji Chi-Square. Variabel yang diukur adalah pengetahuan, sikap, perilaku penggunaan PLD, dan ambang dengar frekuensi bicara. Hasil penelitian menunjukkan adanya hubungan antara pengetahuan penggunaan PLD dengan ambang dengar frekuensi bicara (p-value < 0,05). Sebaliknya, sikap dan perilaku tidak didapatkan hubungan dengan ambang dengar frekuensi bicara (p-value > 0,05). Penelitian ini menyimpulkan bahwa terdapat kejadian gangguan pendengaran pada mahasiswa pada tahun kedua pandemi karena berbagai sebab, termasuk penggunaan PLD. Terdapat pengaruh antara pengetahuan tentang penggunaan PLD berlebihan yang dapat menyebabkan gangguan pendengaran. Tidak ada pengaruh sikap dan perilaku penggunaan PLD terhadap ambang dengar frekuensi bicara. Kata Kunci: pengetahuan, sikap, perilaku, PLD, frekuensi bicara Dimensions Index : https://app.dimensions.ai/details/publication/pub.1154332707 Data Availability Statement: The original contributions presented in the study are included in the article/Supplementary Material, further inquiries can be directed to corresponding author/s. Supplementary Material : https://altera.ub.ac.id/index.php/altera/article/view/10